Kinetics and mechanism for hydrothermal conversion of polyhydroxybutyrate (PHB) for wastewater valorization. Issue 20 (25th September 2019) - Li, Yalin; Strathmann, Timothy J.
Abstract : Investigation of reaction mechanism and development of a kinetics network model for hydrothermal conversion of polyhydroxybutyrate (PHB) for wastewater valorization. Abstract : Conventional wastewater treatment processes can be tailored to recover organic carbon from wastewater as intracellular polyhydroxybutyrate (PHB) polymer granules while simultaneously meeting effluent discharge standards. Traditional applications of PHB as a bioplastic are hampered by its suboptimal properties ( e.g., brittle), lack of efficient and sustainable approaches for recovering PHB from cells, and concerns about wastewater-derived impurities. In this study, we report on the conversion of PHB and its monomer acids – 3-hydroxybutyric acid (3HBA) and crotonic acid (CA) – under hydrothermal conditions (in condensed water at elevated temperature and pressure) to form propylene, a valuable chemical intermediate that self-separates from water. PHB depolymerization results in a mixture of 3HBA and CA, which can interconvert via (de)hydration reactions that vary with prevailing reaction conditions. Further hydrothermal conversion of the monomer acids yields propylene and CO2 . Conversion of 3HBA occurs at lower temperatures than CA, and a new concerted dehydration-decarboxylation pathway is proposed, which differs from the sequential dehydration (3HBA to CA) and decarboxylation (CA to propylene and CO2 ) pathway reported for dry thermal conversion. A kinetics network model informed by experimental results reveals that CA conversion to propylene and CO2 proceeds predominantly via hydration to 3HBA followed by the concerted dehydration-decarboxylation pathway rather than by direct decarboxylation of CA. Demonstrative experiments using PHB-containing methanotrophic biomass show results consistent with the model, producing propylene at near-theoretical yields at lower temperatures than reported previously.